Increasing Demand of Samgyeopsal Restaurants in Meeting Service Quality Dimension in Novaliches, Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the increasing demand of Samgyeopsal Restaurantsin meeting the service quality in Novaliches, Quezon City, in terms of age, gender, salaryincome, community profile, frequent visits, price range, and proximity.The results of the study reveal that the element affecting the increasing demand forSamgyeopsal restaurant in terms of the price of related goods, preference of the consumer,and expectation in service and goods is "Agree." The assessment of the service quality ofSamgyeopsal restaurant in terms of reliability/assurance, empathy, and tangibles is "Agree."The problems encountered by Samgyeopsal restaurants in meeting service quality are price,food flavor, quality service, time consumption, quick service, and visual facilities. Overall, theresearchers recommend to improve dealing with customer complaints and concerns,employees must have better training for quality service and fast and efficient service thatconsumes the time of customers to increase the demand.
Keywords: Business